THE EFFECT OF STRONG ANISOTROPIC SCATTERING ON THE CRITICAL SPHERE PROBLEM IN NEUTRON-TRANSPORT THEORY USING A SYNTHETIC KERNEL - YILDIZ, C; ALCAN, E (PERGAMON-ELSEVIER SCIENCE LTD, 1995)
The effect of strong anisotropic scattering law on the variation of the critical radius in one-speed neutron transport theory is studied using a synthetic kernel. Numerical results for the critical radius are obtained and tabulated for selected illustrative cases. The results indicate that low-order Legendre approximations are sufficient to show the effect of anisotropic scattering on the variation of the critical radius.
Keywords: ISOTROPIC SCATTERING; CRITICAL SLAB; FN METHOD; BACKWARD; EQUATION; MODEL; Nuclear Science & Technology